CGIAR delivering scientific foundations for peace and security: CGIAR FOCUS Climate Security strategy - Läderach, Peter R.D.; Pacillo, Grazia; Bonilla Findji, Osana; Liebig, Theresa Ines; Ayala Parker, Nina de (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The development of CGIAR FOCUS Climate Security has revealed CGIAR’s untapped potential in Peace and Security. Much of CGIAR’s research contributes to improving the prospects of peace. Taking stock of a CGIAR portfolio analyses and collaborative, high-level webinars - CGIAR FOCUS Climate Security has identified four research areas: Evidence for peace, Programing fo peace, Finance for peace and Policy for peace. Building on the these research areas in partnership with our extensive network, 9 flagship iniciatives have designed for 2021 flagship initiatives, which, if grouped together, make up our roadmap for the year ahead.